2010
DOI: 10.1182/blood-2009-10-250803
|View full text |Cite
|
Sign up to set email alerts
|

Human NLRP3 inflammasome activation is Nox1-4 independent

Abstract: The NLRP3 inflammasome can be activated by pathogen-associated molecular patterns or endogenous danger-associated molecular patterns. The activation of the NLRP3 inflammasome results in proteolytic activation and secretion of cytokines of the interleukin-1 (IL-1) family. The precise mode of activation of the NLRP3 inflammasome is still elusive, but has been postulated to be mediated by reactive oxygen species (ROS) generated by an NADPH oxidase. Using primary cells from chronic granulomatous disease (CGD) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(129 citation statements)
references
References 11 publications
4
125
0
Order By: Relevance
“…32,33 However, this issue remains a matter of debate, because several groups showed that ROS had either no effect or an accelerating effect on inflammasome-mediated IL-1b. [34][35][36] Furthermore, the ROS source and the specific ROS molecule that controls inflammasome activity are not yet characterized. Some investigators favor Phox, 32,34 whereas others implicate alternative sources, such as mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 However, this issue remains a matter of debate, because several groups showed that ROS had either no effect or an accelerating effect on inflammasome-mediated IL-1b. [34][35][36] Furthermore, the ROS source and the specific ROS molecule that controls inflammasome activity are not yet characterized. Some investigators favor Phox, 32,34 whereas others implicate alternative sources, such as mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Although inhibition of ROS production prevents NLRP3 inflammasome activation, the mechanism of ROS production by many NLRP3 stimuli has yet to be fully elucidated. While NADPH oxidase inhibitors, including DPI and apocynin, appear to inhibit NLRP3 activation by many stimuli, including Ad5, genetic approaches have suggested that loss of function of numerous subunits of NADPH oxidase, including gp91 phox , p47 phox , and p22 phox , either enhances or does not affect IL-1␤ release in response to NLRP3 stimuli (33,51). Nonetheless, ROS are known to be produced in response to these NLRP3 stimuli, and NLRP3 activation can be prevented by treatments which prevent ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…9 The TAK1-JNK pathway, which is also modulated by calcium-dependent calcium/calmodulin-dependent protein kinase type II function, is activated through lysosomal rupture and is required for the complete activation of the NLRP3 inflammasome. 9 Although we discuss here common mechanisms, i.e., ROS signaling, 62 K + efflux, 82 and lysosomal destabilization, 55 in terms of NLRP3 inflammasome activation, other pathways, such as purinergic receptor signaling, 104 are being revealed to explain the mechanisms by which diverse stimuli activate the NLRP3 inflammasome complex (Figure 1). …”
Section: Molecular Mechanisms Of the Canonical Activation Of The Nlrpmentioning
confidence: 99%
“…Several studies demonstrated that caspase-1 activation and IL-1b secretion are not affected, and may even be increased, in phagocyte oxidase-defective monocytes in chronic granulomatous disease. [80][81][82] Moreover, macrophages from NOX2-deficient mice dose not fail in the maturation and secretion of IL-1b in response to various signals, including silica crystals, monosodium urate (MSU), ATP, and deoxyadenylic-deoxythymidylic. 57 In superoxide dismutase 1-deficient macrophages and in vivo, increased superoxide generation inhibits caspase-1 activation and cytokine production.…”
Section: Molecular Mechanisms Of the Canonical Activation Of The Nlrpmentioning
confidence: 99%